Selection of pulverized coal fuel components for blast furnaces based on the study of physico-chemical processes during their heating - Fedorov, Sergei; Amdur, Alexey (Journal of Mining and Metallurgy, Section B: Metallurgy, 2024)
There is a global tendency to use technologies related to saving energy costs per unit of production in blast furnace production. This is due to the use of pulverized coal fuel (PCF) instead of part of the coke. The selection of components of the PCF charge from a wide range of carbon-containing materials to expand the raw material base and minimize cost is an important task. One of these materials is peat. The purpose of this work is to develop a methodology for selecting pulverized coal fuel components based on their comprehensive study on the example of milling peat. Industrial experiments were carried out at an operating metallurgical plant. The particle size of PCF is no more than 70-100 μm. Thermal destruction of peat in an inert atmosphere accounts for 59% of the mass loss. The maximum destruction rate is 2.69%/min versus 2.0%/min for long–flame coal. The release of volatile components begins at 425°C for lean coal, 300°C for brown coal and 220°C for peat. The destruction of coal also leads to an increase in the specific surface area. It grows from 2.04 to 161.3 m2/g for brown coal. Combustion accounts for about 27% of the total loss of peat mass, for long-flame coal this value is twice as high. The total thermal effect for coal is in the range from 15510 to 17751 kJ/kg, for peat from 12816 to 14148 kJ/kg. Pulverized coal fuel produced during the pilot period was blown into an industrial blast furnace. The equipment of the PCF feed path, the poppet mill worked stably without changing the operating parameters. There were no deviations in the operation of the blast furnace. Due to the introduction of peat, the consumption of lean coal was reduced. The consumption of PCF and natural gas has practically not changed.